Una fiesta barroca en tiempos de Carlos II : el auto de fe madrileño de 1680 - Vincent Parello (Les Cahiers de Framespa)
Significantly, the 1860 Madrid auto-da-fé is a religious and political dogma for the use of the people. It exalts the values of the monarchical and seigneurial system along with the precepts of the Council of Trent and the ideology of the Counter Reform. Catholicism reveals itself as the enemy of Protestantism, Mahometism and Judaism, whose heresy is materialised in the 104 marranos of Portuguese origin.